“They Are Not Gone – yet!” : Social Media Users’ Reaction to the Perceived Death of Cyber Acquaintances - Memarian, Mohammad (Asian Journal of Media and Communication, 2022)
Through in-depth interviews with 28 Iranian social media users, this paper examines the reaction of social media users to the perceived death of their online friends in order to find common threads of anxieties and uncertainties among users who experienced such events. We found that subjects experience contextual, cognitive and emotional difficulties in absorbing the news, leading them to go through an initial stage of wandering before dealing with the actual trauma. Such difficulties are categorized in terms of 5 generic conditions: Conceptual Dilemma, Rational Denial, Situational Puzzlement, Relational Confusion, and Environmental Inconsistency. With ample examples, we have discussed each condition and their interrelatedness. It seems that rather than an absolute fact, the death of an online friend is understood, or felt, as a fuzzy state of mixed presence and absence, in relation to which later death events in online or even offline situations may be understood.